Botryosphaeria and Related Taxa Causing Oak Canker in Southwestern Spain (Plant Disease, 2003)
ABSTRACT Although root disease caused by Phytophthora cinnamomi is considered to be the most frequent and damaging disease associated with Quercus spp. decline in southwestern Spain, cankers commonly are observed on branches of declining Mediterranean Quercus spp. in this region. In surveys carried out in eight declining Quercus forests, strips of necrotic inner bark were common on diseased branches. Botryosphaeria stevensii, B. dothidea, and Diplodia sarmentorum consistently were isolated from these branches. Isolates of all three species caused cankers when inoculated onto excised Quercus branches. Inoculations on healthy branches in the field also induced canker development, but only B. stevensii caused lesions that girdled and killed the branches. The optimum temperature for in vitro growth of B. stevensii and B. dothidea was above 25°C, with slow growth at 35°C. In contrast, D. sarmentorum had an optimum temperature for growth of about 21°C, and did not grow at 35°C. The common occurrence and wide distribution of these pathogens, their association with cankers, and their ability to infect Quercus spp. suggest that they may contribute to the Quercus spp. decline in southwestern Spain.
doi: 10.1094/PDIS.2003.87.12.1515